STRATEGY OF TRAINING OF FUTURE PRIMARY CLASSES TEACHERS (ON THE EXAMPLE OF MARIUPOL STATE UNIVERSITY) - Timofieieva, Irina; Netreba, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The strategy of training future primary school teachers is analyzed in the article. That is relevant in the context of the Concept of the New Ukrainian School. In this regard, the purpose of the article is to disclose the tasks and content of the strategy of future primary teachers’ training in Mariupol State University. The main research methods to achieve the goal were selected: questioning of students that contains a list of questions of different categories; survey of specialists, who provide training for future primary school teachers, was made up of introductory and informational questions.Successful implementation of these goals and objectives of the strategy is being introduced by teachers of the pedagogical and education chair of Mariupol State University: the development of basic and applied research in the field of professional education of future primary school teachers is provided, innovative methodological manuals are developed, and researches with talented youth are being organized.